Analysis of the Influence of Excitation Frequency on Nonlinear Dynamics of the Shift Planetary Transmission System - Wu Xiaolong; Du Yaosen; Gao Pengju; Wang Xiaosai (Jixie chuandong)
Gear shifting mechanism is one of the most critical components in the shifting transmission system, and its performance directly affects the power performance and stability of the transmission system. In this study, the dynamic equations of the gear shifting mechanism of the two-stage planetary gear transmission system are established, and the influence of the external excitation frequency on the complex dynamic characteristics of the transmission system is studied. Through bifurcation diagram, time domain response diagram, phase diagram, Poincare section diagram and spectrum diagram, the chaotic vibration characteristics of the two-stage planetary gear transmission system are learned, and the stable vibration range of the external excitation frequency is obtained. The proportional differential control method is used to control the chaotic vibration of the gear shifting mechanism, and the chaotic vibration is adjusted to a stable single period vibration. The research results lay a foundation for improving the stability of the shift planetary transmission system.